العولمة: انتصار للغموض - فيلالي, صالح (Sciences de l'Homme et de la Société; Vol. 3 (2012): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2012)
يناقش هذا المقال مفهوم العولمة من منظور سوسيولوجي، مشيرا إلى أن هذا المفهوم مازال يسوده الغموض في الدراسات السوسيولوجية، الأمر الذي يعيق بصورة جدية تقدم الدراسات الأمبريقية في هذا المجال. ولتجاوز هذا الاشكال يطرح المقال ثلاث جدليات يتصف بها النقاش السوسيولوجي حول مفهوم العولمة.          This article addresses the concept of globalization from a sociological perspective, pointing out that this concept is still unclear in sociological studies, which seriously impedes progress empirical studies in this topic. In order to avoid this problem the article poses three arguments characterized by sociological debates around the concept of globalisation.